DECOY EFFECT, COGNITIVE LOAD, AND POSITIVE EMOTION ON PURCHASE INTENTION: IPHONE 14 CASE STUDY - Farrell Ionwyn Eduardo; Nelly, Nelly; Jonathan Kenny Juen; Lina, Lina; Ratnawati, Ratnawati (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2025)
Understanding the psychological factors influencing consumer behavior is a essential for enhancing purchase intention. This study examines the impact of positive emotion as a mediator between purchase intention and cognitive load or the decoy effect. Utilizing a quantitative methodology, data were collected using a questionnaire and analyzed with the PLS-SEM technique using SmartPLS. A purposive sampling method yielded 129 iPhone 14 users as respondents for this study. The findings indicate that the decoy effect and cognitive load has a significant impact on purchase intention when mediated by positive emotion. These results underscore the importance of minimizing cognitive load and leveraging the decoy effect in marketing practices.